The cultural politics of human rights : comparing the US and UK / Kate Nash. - Nash, Kate, 1958- (Cambridge University Press, 2009)
How does culture make a difference to the realisation of human rights in Western states? It is only through cultural politics that human rights may become more than abstract moral ideals, protecting human beings from state violence and advancing protection from starvation and the social destruction of poverty. Using an innovative methodology, this book maps the emergent 'intermestic' human rights field within the US and UK in order to investigate detailed case studies of the cultural politics of human rights. Kate Nash researches how the authority to define human rights is being created within states as a result of international human rights commitments. Through comparative case studies, she explores how cultural politics is affecting state transformation today.